2017
DOI: 10.1002/tal.1362
|View full text |Cite
|
Sign up to set email alerts
|

On the evaluation of wind loads for wind turbines' foundation design: Experimental and numerical investigations

Abstract: Summary In the past two decades, wind farms have been enjoying renewed interest as means for clean and renewable energy production. Larger and taller wind turbines are used for harvesting wind energy. In this paper, a boundary‐layer wind tunnel experiment was carried out on a model of the 5‐MW National Renewable Energy Laboratory (NREL) wind turbine, to evaluate overall wind‐induced base loadings in a parked condition. While mean and background base loadings were measured experimentally, a posttest dynamic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The system was defined based on the properties of the wind turbine in parked position excited by a filtered band limited Gaussian white noise. The filter was designed such that the excitation force following the experimental originated data of a wind turbine in a parked position . Figure shows the measured wind load spectrum extracted from Abdelkader et al and the spectrum of a filtered white noise excitation.…”
Section: Semiactive Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…The system was defined based on the properties of the wind turbine in parked position excited by a filtered band limited Gaussian white noise. The filter was designed such that the excitation force following the experimental originated data of a wind turbine in a parked position . Figure shows the measured wind load spectrum extracted from Abdelkader et al and the spectrum of a filtered white noise excitation.…”
Section: Semiactive Controllermentioning
confidence: 99%
“…The filter was designed such that the excitation force following the experimental originated data of a wind turbine in a parked position . Figure shows the measured wind load spectrum extracted from Abdelkader et al and the spectrum of a filtered white noise excitation. An appropriate bandpass IIR Butterworth digital filter has been used to filter the band‐limited Gaussian white noise inputs and make it to follow the experimental spectrum.…”
Section: Semiactive Controllermentioning
confidence: 99%
“…Using a numerical model, Abhinav and Saha [26] studied the effects of soil stiffness and pile parameters on the natural frequency and amplitude of the response. Abdelkader et al [27] showed that the existence of a foundation may reduce wind loads, and they assumed that a fixed foundation leads to a conservative design. Thus, ground conditions impact the natural frequency and damping ratio of MWTs, which further affect structural responses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the variability in wind direction also affects the fetch length and therefore, the wave propagation schemes and sea-state intensity [42], as well as the estimation of wind and/or wave design values [43,44]. The probabilistic modeling of wind direction seems to be increasingly important for wind farm design and micro-siting, both onshore and offshore [45][46][47], for structural stability and reliability [48][49][50] and long-term economic gains from such applications [51].…”
Section: Introductionmentioning
confidence: 99%